Chitosan-collagen based film for controlled delivery of a combination of short life anesthetics - Di Martino, Antonio; Drannikov, Alexander; Surgutskaia, Natalia S; Ozaltin, Kadir; Postnikov, Pavel S; Marina, Trusova E; Sedlarik, Vladimir (International journal of biological macromolecules, 2019)
The present research was undertaken to develop a chitosan-collagen film for controlled delivery of combinations of local anesthetics. The film has been prepared by casting which is a versatile, rapid and low-cost approach distinguished by high reproducibility. The mechanical, morphological, and physicochemical properties of the films and the impact of the drug loading were evaluated. We showed that the formulations have a good combination of strength and flexibility with high water permeability. Surface morphology investigation indicates a variation in roughness depending on the loaded compound. Release studies were performed in controlled environments and the data processed by the Higuchi model to assess the dynamics of the release. The local anesthetics, lidocaine, tetracaine, and benzocaine, were uniformly distributed within the matrix and released in a rate and magnitude specific for the drug concentration and combination tunable in a range time from 6 h to 24 h. The films dissolve completely in the physiological environment within 24 h without leaving any toxic metabolites as both of the components are recognized as safe. In vitro cytotoxicity and cell proliferation tests performed on human dermal fibroblast demonstrate the biocompatibility and lack of cytotoxicity of the prepared formulations.
Keywords: Cell Survival; Chitosan; Tetracaine; Humans; povrchové vlastnosti; permeabilita; Delayed-Action Preparations; molekulová hmotnost; Permeability; pára; buněčná smrt; viabilita buněk; Molecular Weight; Drug Delivery Systems; lidé; kolagen; zvířata; proliferace buněk; Anesthetics, Local; Collagen; Drug Liberation; uvolňování léčiv; benzokain; difuze; Kinetics; Cattle; Diffusion; Film; Cell Proliferation; lékové transportní systémy; skot; Hydrogen-Ion Concentration; Surface Properties; léky s prodlouženým účinkem; anestetika lokální; lidokain; Drug delivery; Steam; fibroblasty; Animals; Local anesthetic; koncentrace vodíkových iontů; chitosan; tetrakain; Cell Death; Lidocaine; kinetika; Fibroblasts; Benzocaine